Customer Perceptions of a Restaurant-Based Healthy Eating Program and Factors Associated with Healthy Food Selection in Restaurants. - Knapp, Megan Bush; Moore, Tamecia; Lederer, Alyssa; Kimball, Molly; Myers, Leann; Johnson, Carolyn (American Journal of Health Education)
Background: Restaurant-based interventions are a promising strategy to improve community food environments and customer food choices. Purpose: Describe the extent to which a restaurant-based program, Ochsner Eat Fit (EF), may influence healthier food choices, and identify factors associated with EF food item selection. Methods: Cross-sectional intercept surveys with 608 customers in 34 EF restaurants. Results: Of 608 respondents, 17.3% ordered an EF item. Of 307 respondents familiar with EF, 89.6% believed EF can help them make healthier food choices. Respondents who agreed the restaurant environment supported healthy choices were 3.4 times more likely to order EF than those who did not agree (95%CI:1.5–7.7, p =.003); African American respondents were 2.1 times more likely than White respondents (95%CI:1.1–3.7, p =.017); and customers trying to make dietary changes were 4 times more likely than those who were not (95%CI:1.2–13.1, p =.024). Discussion: Customers believed EF can positively influence food choices. Race, desire to make dietary changes, beliefs about healthy foods, and perceptions of the restaurant environment were associated with food choices. Future programming efforts should consider increasing the number and promotion of healthy options to support healthy decision-making. Translation to Health Education Practice: Findings can be used to inform the development of restaurant-based healthy eating programs.